A parallel algorithm of LU factorization - Čiegis, Raimondas; Starikovičius, Vadimas (Lietuvos matematikos rinkinys, 1998)
This paper discusses issues in the design of LU factorization parallel algorithm on distributed memory parallel computers. A new cyclic distribution method is proposed for heterogeneous parallel computers, which include virtual parallel computers. The efficiency of the algorithm is investigated and results of computational experiments are given.